(untitled) (Trabalho & Educação, 2017)
This article aims to analyze the teaching work in the context of distance education to highlight possible indicators of precariousness in the organization of teaching work in this kind of teaching. Therefore, in this study, a questionnaire was applied with 13 questions focusing on academic degree, type of bond, working day and working conditions. A total of 115 professors participated, of which 10 were graduates (8.7%), 63 postgraduates (54.8%), 29 with master degree (25.2%) and 13 with doctorate (11.3%). Public institutions (30.4%) and private institutions (69.6%). More than a third of these professionals (37.4%) carry out activities without a formal employment relationship with the institutions, in the public as a scholarship recipient, and in private institutions as autonomous ones. The work in distance education is done as a way of complementing income and with a refined division of labor, on the one hand, and on the other, by large wage discrepancies and guarantee of labor rights. Thus, teaching work in the context of new technologies points to an intensification of precariousness, fragmentation of the category, and the weakening of formal work relations. ___ O presente artigo objetiva analisar o trabalho docente no contexto da educação a distância com vistas a evidenciar possíveis indicadores de precarização na organização do trabalho docente nesta modalidade de ensino. Para tanto, neste estudo foi aplicado um questionário com 13 questões enfocando titulação, tipo de vínculo, jornada e condições de trabalho. Participaram da pesquisa 115 docentes, sendo 10 graduados (8,7%), 63 especialistas (54,8%), 29 mestres (25,2%) e 13 doutores (11,3%) distribuídos nas funções de professor, tutor e conteudista, em instituições públicas (30,4%) e privadas (69,6%). Mais de um terço desses profissionais (37,4%) exercem as atividades sem vínculo formal de trabalho com as instituições, nas públicas como bolsistas e nas instituições privadas como autônomos. O trabalho em educação a distância é feito, por um lado, como modo de complementação de renda e com uma refinada divisão do trabalho, e por outro, com grandes discrepâncias salarias e de garantia de direitos trabalhistas. Assim sendo, o trabalho docente, no contexto das novas tecnologias, aponta para uma intensificação da precarização, fragmentação da categoria e a fragilização das relações formais de trabalho.